Effects of Heat Treatment on Morphology, Texture, and Mechanical Properties of a Mnsial Multiphase Steel with Trip Behavior - Monsalve-Gonzalez, A; Artigas-Abuin, A; Castro-Cerda, F; Salinas-Gaona, A (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
The effect that the microstructure exerts on the Transformation-Induced Plasticity (TRIP) phenomenon and on the mechanical properties in a multiphase steel was studied. Samples of an initially cold-rolled ferrite–pearlite steel underwent different intercritical annealing treatments at 750◦C until equal fractions of austenite/ferrite were reached; the intercritical treatment was followed by isothermal bainitic treatments before cooling the samples to room temperature. Samples in the first treatment were heated directly to the intercritical temperature, whereas other samples were heated to either 900◦C or 1100◦C to obtain a fully homogenized, single-phase austenitic microstructure before performing the intercritical treatment. The high-temperature homogenization of austenite resulted in a decrease in its stability, so a considerable austenite fraction transformed into martensite by cooling to room temperature after the bainitic heat treatment. Most of the retained austenite transformed during the tensile tests, and, consequently, the previously homogenized steels showed the highest Ultimate Tensile Strength (UTS). In turn, the steel with a ferritic–pearlitic initial microstructure exhibited higher ductility than the other steels and texture components that favor forming processes. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.